Pengaruh Model Pembelajaran CORE (Connecting, Organizing, Reflecting, Extending) Terhadap Kemampuan Koneksi Matematis Siswa Kelas VIII SMP N 3 Rambah - Mardiana; Hera Deswita; Ratri Isharyadi (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2020)
The low ability of students' mathematical connections were caused by the lack of application of learning with previous material and the tendency of students to memorize concepts or formulas. The purpose of this study was to see whether there was an influence of the CORE learning model on the mathematical connection ability of Grade VIII students of SMPN 3 Rambah. This type of research was a quasi-experimental research (quasi-experimental) with a Two-Group Posttest Only research design. The population of this study were eighth grade students of SMPN 3 Rambah. Sampling uses simple random sampling technique, so that class VIII.3 were obtained as the experimental class and class VIII.1 as the control class. In the experimental class CORE learning models are applied, whereas in the control class conventional learning was applied. The data of mathematical connection ability were obtained by the test technique. The instrument used is a matter of tests of mathematical connection ability that has been valid and reliable. Data analysis was performed for hypothesis testing. Based on the prerequisite test results obtained that hypothesis testing was done by the Mann Whitney test. The calculation results obtained are 3.81 > 1.96 with a value, then reject H0 so that it can be concluded that there was an effect of the CORE learning model on the mathematical connection ability of class VIII students of SMPN 3 Rambah.